Centre‐level variation in treatment and outcomes and predictors of outcomes in 5‐year‐old children with non‐syndromic unilateral cleft lip treated within a centralized service: the Cleft Care UK study. Part 6: summary and implications. (June 2017) - Ness, A. R.; Wills, A. K.; Mahmoud, O.; Hall, A.; Sell, D.; Smallridge, J.; Southby, L.; Stokes, D.; Toms, S.; Waylen, A.; Wren, Y.; Sandy, J. R.
Structured Abstract: Objectives: To summarize and discuss centre‐level variation across a range of treatment and outcome measures and examine individual and ecological determinants of outcome in children in Cleft Care UK (CCUK). Setting and sample population: Two hundred and sixty‐eight 5‐year‐old British children with non‐syndromic unilateral cleft lip and palate (UCLP) recruited to CCUK and treated within a centralized service. Materials and Methods: Children had a range of treatment and outcome measures collected at a 5‐year audit clinic. These outcomes included dento‐alveolar arch relationships from study models, measures of facial appearance from cropped photographs, hearing loss from audiological assessment, speech from speech recordings, self‐confidence and strengths and difficulties from parental self‐report. Data were collected on educational attainment at age 7 using record linkage. Centre variation was examined using hierarchical regression and associations between variables were examined using logistic or poisson regression. Results: There was centre‐level variation for some treatments (early grommet placement, fitting of hearing aids, fluoride treatment, secondary speech surgery and treatment for cleft speech characteristics) and for some outcomes (intelligibility of speech). Hearing loss was associated with a higher risk of poor speech while speech therapy was associated with a lower risk of poor speech. Children had high levels of caries but levels of preventative treatment (fluoride varnish and tablets) were low. Conclusions: Further improvements to and monitoring of the current centralized model of care are required to ensure the best outcomes for all children with cleft lip and palate.